A Three-Generation Family with Idiopathic Facial Palsy Suggesting an Autosomal Dominant Inheritance with High Penetrance - Christian Grønhøj Larsen; Mette Gyldenløve; Aia Elise Jønch; Birgitte Charabi; Zeynep Tümer (Case Reports in Otolaryngology)
Idiopathic facial palsy (IFP), also known as Bell’s palsy, is a common neurologic disorder, but recurrent and familial forms are rare. This case series presents a three-generation family with idiopathic facial palsy. The mode of inheritance of IFP has previously been suggested as autosomal dominant with low or variable penetrance, but the present family indicates an autosomal dominant trait with high or complete penetrance. Chromosome microarray studies did not reveal a pathogenic copy number variation, which could enable identification of a candidate gene.